1976
DOI: 10.1152/jappl.1976.40.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Hypoventilation in ponies after carotid body denervation

Abstract: Seven ponies were subjected to carotid body denervation (CD) and two ponies were sham operated (S). Measurement of arterial blood gases and arterial blood and cerebrospinal fluid (CSF) acid-base balance were made prior to and 1,2,4,9, and 17 wks after surgery in unanesthetized animals. Resting ventilation and ventilatory responsiveness to hypoxia and NaCN infusion were assessed prior to and 2,9, and 17 wks after surgery. Alveolar hypoventilation in the CD ponies was marked 1-2 wk after surgery when VE and VA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 0 publications
6
43
0
Order By: Relevance
“…In the present work we have studied the effects of 8 and 15 days duration IH of moderate intensity as defined by nadir arterial PO 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work we have studied the effects of 8 and 15 days duration IH of moderate intensity as defined by nadir arterial PO 2 …”
Section: Discussionmentioning
confidence: 99%
“…Each obstruction produces a fall in arterial PO 2 Exposure to intermittent hypoxia. Four rats were housed in hermetically shielding transparent methacrylate chambers (16 l), along with food and water.…”
mentioning
confidence: 99%
“…In cats (88) and rats (11,60,82), there is considerable recovery in the chemoreflex a few weeks after CBD and near total recovery a year later. In dogs (80), ponies (8,9), and goats (31,75), there is no significant or only a small recovery a few weeks after CBD, and in ponies there is less than 25% recovery 4 yr after CBD (Fig. 1).…”
Section: Denervation Of Peripheral Chemoreceptorsmentioning
confidence: 99%
“…After CBD, breathing and/or hypoventilation is shown to be initially reduced during room air breathing at rest (8,9,25,26,57,75,80,83) (Fig. 1) and during exercise (74,75,77), but there is plasticity or recovery from the hypoventilation (Fig.…”
Section: Denervation Of Peripheral Chemoreceptorsmentioning
confidence: 99%
“…Although no clear physiologic role for these carotid body monoamines has been established, recent studies have demonstrated that dopamine may act as an inhibitor of carotid bodies chemosensitivity (22)(23)(24). Exogenous catecholamines can change the sensitivity of chemoreceptors to hypoxia and hypercapnia (25), which might be due to an action on excitatory and inhibitory dopaminergic receptors (26). One might speculate that the absence of a terbutaline effect on the respiratory response to LCR stimulation in the younger lambs shortly after birth is related to the presence of already high catecholamine concentrations in their carotid bodies.…”
Section: O-l_l-----'lllj"--------'--_jmentioning
confidence: 99%